2011
DOI: 10.1021/nn102752a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Gold Nanoclusters as a Biocompatible Marker for In Vitro and In Vivo Tracking of Endothelial Cells

Abstract: We have been investigating the fluorescent property and biocompatibility of novel fluorescent gold nanoclusters (FANC) in human aortic endothelial cells (HAEC) and endothelial progenitor cells (EPC). FANC (50-1000 nmol/L) was delivered into cells via the liposome complex. The fluorescence lasted for at least 28 days with a half-life of 9 days in vitro. Examination of 12 transcripts regulating the essential function of endothelial cells after a 72 h delivery showed that only the vascular cell adhesion molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 36 publications
0
130
1
Order By: Relevance
“…For instance, the Mattoussi lab reported the preparation of red-emitting Au NCs with a quantum yield of up to 14% when stabilised with bidentate thiolated ligands containing a zwitterionic group 40 . NC features such as tunable photoluminescence [41][42] , multiexponential fluorescence lifetime [43][44] , or aggregation induced enhancement 45 have been extensively studied with potential applications in the fields of sensing 46 , bioimaging 47 and optics 48 . Other interesting properties of NCs relevant for therapeutic applications rely on their ultra-small size, low toxicity and stability in physiological media.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Mattoussi lab reported the preparation of red-emitting Au NCs with a quantum yield of up to 14% when stabilised with bidentate thiolated ligands containing a zwitterionic group 40 . NC features such as tunable photoluminescence [41][42] , multiexponential fluorescence lifetime [43][44] , or aggregation induced enhancement 45 have been extensively studied with potential applications in the fields of sensing 46 , bioimaging 47 and optics 48 . Other interesting properties of NCs relevant for therapeutic applications rely on their ultra-small size, low toxicity and stability in physiological media.…”
Section: Introductionmentioning
confidence: 99%
“…16À19 For example, Yeh et al reported°uorescent Au NCs as a biocompatible marker for in vitro and in vivo tracking of endothelial cells; DNA-encapsulated°uorescent silver NCs could be used as biolabels. 18,19 However, to date extensive researches for NCs focused on luminescent Au and Ag nanomaterials. 20À22 Studies for the synthesis, properties and applications of Cu NCs are still scarce primarily because of the di±-culties in preparation of the highly stable and extremely small particles.…”
Section: Introductionmentioning
confidence: 99%
“…Human EPCs were used in accordance with the study protocol, (24,25) which was approved by the Institutional Review Board of Mackay Medical College, New Taipei City, Taiwan (reference number: P1000002). All subjects gave informed written consent before enrolling in the study.…”
Section: Cell Culturementioning
confidence: 99%